Knowledge acquisition process as an issue in information sciences (Libellarium: journal for research in the field of information and related sciences, 2016)
The paper presents an overview of some problems of information science which are explicitly portrayed in literature. It covers the following issues: information explosion, information flood and data deluge, information retrieval and relevance of information, and finally, the problem of scientific communication. The purpose of this paper is to explain why knowledge acquisition, can be considered as an issue in information sciences. The existing theoretical foundation within the information sciences, i.e. the DIKW hierarchy and its key concepts - data, information, knowledge and wisdom, is recognized as a symbolic representation as well as the theoretical foundation of the knowledge acquisition process. Moreover, it seems that the relationship between the DIKW hierarchy and the knowledge acquisition process is essential for a stronger foundation of information sciences in the 'body' of the overall human knowledge. In addition, the history of both the human and machine knowledge acquisition has been considered, as well as a proposal that the DIKW hierarchy take place as a symbol of general knowledge acquisition process, which could equally relate to both human and machine knowledge acquisition. To achieve this goal, it is necessary to modify the existing concept of the DIKW hierarchy. The appropriate modification of the DIKW hierarchy (one of which is presented in this paper) could result in a much more solid theoretical foundation of the knowledge acquisition process and information sciences as a whole.The theoretical assumptions on which the knowledge acquisition process may be established as a problem of information science are presented at the end of the paper. The knowledge acquisition process does not necessarily have to be the subject of epistemology. It may establish a stronger link between the concepts of data and knowledge; furthermore, it can be used in the context of scientific research, but on the more primitive level than conducting of scientific methods. Moreover, the description of this process, as opposed to other problems of information sciences, necessarily involves all four DIKW concepts. Finally, the solution of this problem may result in a more complete theory of information.
Keywords: knowledge acquisition; knowledge acquisition process; information; data; knowledge; DIKW hierarchy